2009
DOI: 10.1038/modpathol.2009.6
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transporter-1 in pulmonary neuroendocrine carcinomas: expression and survival analysis

Abstract: Glucose transporter-1 (GLUT-1) mediates the transport of glucose across the cellular membrane. Its elevated levels and/or activation have been shown to be associated with malignancy. The aim of this study was to investigate GLUT-1 expression in pulmonary neuroendocrine carcinomas. Tissue microarray-based samples of 178 neuroendocrine carcinomas, including 48 typical carcinoids, 31 atypical carcinoids, 27 large cell neuroendocrine carcinomas and 72 small cell carcinomas from different patients, were studied imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…Glut1 was highly expressed in patients with LCNEC and SCLC, but Glut3 expression was low in pulmonary NE tumors. Ozbudak et al has documented that Glut1 expression was observed in 7% of TC, 74% of LCNEC and 78% of SCLC, and significantly correlated with neuroendocrine differentiation/tumor type and poor prognosis (20). In addition, a statistically significant difference in the prognosis according to Glut1 expression was seen for stage I-II (p<0.001) but not stage III-IV (p=0.4) neuroendocrine carcinomas.…”
Section: Discussionmentioning
confidence: 97%
“…Glut1 was highly expressed in patients with LCNEC and SCLC, but Glut3 expression was low in pulmonary NE tumors. Ozbudak et al has documented that Glut1 expression was observed in 7% of TC, 74% of LCNEC and 78% of SCLC, and significantly correlated with neuroendocrine differentiation/tumor type and poor prognosis (20). In addition, a statistically significant difference in the prognosis according to Glut1 expression was seen for stage I-II (p<0.001) but not stage III-IV (p=0.4) neuroendocrine carcinomas.…”
Section: Discussionmentioning
confidence: 97%
“…All the genes specifically targeted in these pathways have been associated with cancer. Some of them have already been linked to neuroendocrine neoplasms: SLC2A1, coding for the glucose transporter 1, has already been reported in lung neuroendocrine tumors as being positively associated with adverse outcome [22]; RPS6KA3, coding for ribosomal protein S6 kinase, is a pivotal molecule in the mTOR pathway [23], which is overactivated in the majority of lung carcinoids [24]; IGF1R and IRS2 belong to the IGF receptor type 1 pathway and have been shown to be active in neuroendocrine cancer cells [25]. Among others, 3 genes were of particular interest, since all have already been demonstrated to be strongly associated with cancer but have never been investigated in neuroendocrine neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…9,16,17 Glucose transporters are overexpressed in hepatocarcinomas, breast cancer, neuroendocrine carcinomas, lymphoblastic leukemia and others. [18][19][20][21] It has been proposed that the high glucose uptake in cancer cells favors cell proliferation more than energy production because glucose metabolism mainly supports fatty acid and ribose-5-phosphate synthesis 5,22 ( Fig. 1).…”
Section: Warburg Effect or Aerobic Glycolysismentioning
confidence: 99%